Case report: A case of epidermolysis bullosa acquisita with IgG and IgM anti-basement membrane zone antibodies relapsed after COVID-19 mRNA vaccination - Minakawa, Satoko; Matsuzaki, Yasushi; Yao, Shogo; Sagara, Chihiro; Akasaka, Eijiro; Koga, Hiroshi; Ishii, Norito; Hashimoto, Takashi; Sawamura, Daisuke (Frontiers in Medicine, 2023)
We report a case of autoimmune bullous disease (AIBD) with IgG and IgM autoantibodies against epidermal basement membrane zone (BMZ), which showed recurrence of mucocutaneous lesions after coronavirus disease 2019 (COVID-19) mRNA vaccination. A 20-year-old Japanese woman with a 4-year history of epidermolysis bullosa acquisita (EBA) presented to our clinic. She noticed fever and rash on the same day and visited at our hospital 2 days later. Physical examination revealed blisters, erosions and erythema on the face, shoulder, back, upper arms, and lower lip. A skin biopsy from the forehead showed subepidermal blister. Direct immunofluorescence showed linear depositions of IgG, IgM, and C3c in the epidermal BMZ. By indirect immunofluorescence of 1M NaCl-split normal human skin, circulating IgG autoantibodies were bound to the dermal side of the split at 1:40 serum dilution, and circulating IgM antibodies were bound to the epidermal side of the spilt. After the increase of prednisolone dose to 15 mg/day, the mucocutaneous lesions resolved in a week. The present case is the first case of possible EBA with IgG and IgM anti-BMZ antibodies, in which the mucocutaneous lesions were recurred after COVID-19 mRNA vaccination. Clinicians should be aware that bullous pemphigoid-like AIBDs, including EBA and IgM pemphigoid, might be developed after COVID-19 mRNA vaccination.